Cadre Mentoring in Reproductive Health Education for Adolescent Girls at Puskesmas Panambungan Makassar - Asyima Asyima; Fatmawati Amir; Fauziah Botutihe; Selvi Selvi; Rahma Winahyun Jannata; Nur Putri Aulia Aulia (Universitas AMIKOM Yogyakarta, 2025)
Adolescent girls' reproductive health remains a critical public health issue, particularly in communities with limited access to information and services. Low literacy regarding menstruation, dysmenorrhea, and reproductive hygiene makes adolescent girls vulnerable to misconceptions and inappropriate health-seeking behavior. Socio-cultural stigma further compounds the problem, preventing open discussion on reproductive health topics. This community service program aimed to empower health cadres at Puskesmas Panambungan, Makassar, as educators in adolescent reproductive health through structured short-course training and participatory extension activities. The program was conducted from May 5–10, 2025, involving 30 active cadres. Methods included cadre capacity building through lectures, interactive discussions using PowerPoint and leaflet media, as well as pre-test and post-test evaluation. Results showed a 65% increase in cadre knowledge after the intervention. Participants were actively engaged, asking questions and sharing personal experiences related to menstruation and reproductive hygiene. Cadres demonstrated their readiness to serve as facilitators and motivators for adolescent girls in their communities. These findings confirm that structured cadre mentoring combining participatory approaches and visual media is an effective strategy for improving adolescent reproductive health literacy in resource-limited settings.